Effects of thermal treatment on walnut detection and allergenicity. (28th November 2018) - Vencia, Walter; Minale, Paola; Migone, Laura; Lazzara, Fabrizio; Vito, Guendalina; Ferrari, Angelo; Razzuoli, Elisabetta
Abstract: BACKGROUND: Peanuts and tree nut allergies pose an increasing food safety problem. The aim of our study was to test the accuracy of different commercial enzyme‐linked immunosorbent assay (ELISA) kits in the detection of the presence of walnuts in untreated and heat exposed food samples. The effects of thermal treatment of samples were evaluated by exposing walnuts to different heat treatments. All samples were first analysed by two different commercial ELISA assays. Then, we performed a skin prick test (SPT) on nine patients with proven nut allergy using small walnut pieces from raw and treated samples. RESULTS: The presence of nuts proteins in thermally processed foods was not accurately detected by ELISA kits. All patients had a positive SPT reaction with raw walnut, while thermal treatments affected walnut allergenicity. The ELISA test gives a negative result in the case of strong thermal treatment, but at the same time allergic subjects react positively to stimulation with the same sample. CONCLUSION: This study suggests that commercial ELISA kits may not be able to accurately determine the amount of proteins present in thermally processed foods due to changes in the solubility and immunoreactivity of the target proteins. Finally, the clinical results highlight that thermal treatment might induce a reduction in walnut allergenicity. © 2018 Society of Chemical Industry